Menjadi Fotografer dengan Kamera Sederhana - Agnes Paulina Gunawan (Bina Nusantara University, 2010)
With the advanced technology in this era, everybody must be quite familiar with the use of camera to take pictures, with different types of SLR camera or pocket camera, digital or manual, with very economic pricing to the most expensive ones, and even the camera which has become one of the features in cell phone. Eventhough there is a very easy access to photography, if one photographer does it without enough knowledge and technique of good photography, sometimes he will not be satisfied with the results. It will be best if a photographer understands a bit of the theories, so he can anticipate any problems which are sometimes caused by the limited features in some not so advanced cameras. And with several tips and tricks of the basic understanding in photography, he will be able to avoid such issues.